Problems of professional training of doctors of general practice – family medicine in the system of postgraduate education. - S. A. Mokiya-Serbina; T. V. Litvinova; N. I. Zabolotnyaya; S. V. Tsyktor (Medičnì Perspektivi)
The article reveals the problems of professional training of family doctors arising in the implementation of measures on preserving and promoting health, preventing diseases in children and adolescents. At present, the doctors of the first level are not able to organize and realize the entire complex of medical and social assistance in the ambulatory clinic at the proper level. The improvement of postgraduate training of family doctors in the field of outpatient pediatric care has been suggested. At the same time, the development of curricula for thematic improvement should be based on studying educational needs of the healthcare system in the region and the ongoing reform processes.